An empirical study: The relationship between personality traits and job performance / Muhazwan Mukhtar - Mukhtar, Muhazwan (Faculty of Business and Management, 2017)
1.1 Background of Study Personality is the element that can influence people. According to Mayer (2007), personality is the arrangement of mental qualities and components inside the person that are sorted out and generally persevering what's more, that impact his or her cooperation's with, and adjustments to, the intrapsychic, physical, and social conditions. Sometimes the personality can derive people to act right or wrong. There have four basic dimensions of personality based on personality traits which is conscientiousness, agreeableness, neuroticism and openness to experience (Velerie, 2012). A good personality will produce an excellence identity. According to (Moreira et aI., 2015), identity was evaluated utilizing the Temperament and Character Inventory. Therefore, personality can be characterized as the combination of characteristic or qualities that from an individual are distinctive character (Suman, 2015) The relationship of personality traits to job performance has created several articles and more than three dozen separate meta-examinations since Barrick and Mount's (1991) influential investigation (Timothy, 2008). According to Laura (2012), Personality traits commonly characterized as descriptions of individuals regarding moderately stable examples of conduct, considerations, and feelings. The relationship between personality and job performance has been as often as possible studied topic in industrial psychology in the previous century (Barrick el at., 200 I). The four of these personality traits can affect the people life. There are four personalities that can affect the human behaviour (Suman, 2012). The first item basic of personality traits is conscientiousness. Conscientiousness means being careful and thorough, preferring to live one's life deliberately. Conscientiousness refers to people who exhibit traits of selfcontrol by methods for being fit for arranging, organizing, working strategically towards goals, and carrying out tasks (Andreas, 2012). It is associated with reliability, hard work, self-discipline, neatness and ambition (Andre, 2008). Conscientiousness is related to having a need for achievement. Secondly is agreeableness. Agreeableness also referred to as likeability, concerns the degree to which individuals are kind, cooperative warm and agreeable versus being cold, rude, harsh and antagonistic (Abu bakar el a!., 2010). Persons may be what we might call too agreeable, in which case they are dependent, overly cooperative and selfeffacing. Thirdly is neuroticism. Neuroticism is the degree to which the individual is calm, self-confident, cool versus insecure, anxious, and depressed and emotional (Abu bakar el a/., 2010). It also refers to understood as the general tendency to experience negative etTects such as fear and difficulties to cope with stress. According to Amirul (2015) neuroticism is the person who tend to be nervous, have a high level of worry about something. Last but not least is openness to experience. Openness to experience means an ability to learn something new, can adapt with different situation or he or she is flexible with any situation, and imagination (Amirul and Mahathir, 2015). Openness to experience also referred to active imagination, aesthetic sensitivity, preference for variety, intellectual curiosity and independence ofjudgment. According to Rae Andrea (2008) people who exhibit openness are likely to be original imaginative, and daring. They also have a broad range of interests, including fantasy. Job performance is a multi-dimensional develop which demonstrates how well representatives perform their tasks, the initiative they take and how they perform to solving the problem (Rothmann and Coetzer, 2003). Job perfonnance could be influenced by silualional components, for example the attributes of the employment, the association and co-workers. According to Rathmann and Coetzer (2003), Job perfonnance could be influenced by silualional components, for example the attributes of the employment, the association and co-workers. According to Rathmann and Coetzer (2003), job performance could be influenced by situational components, for example the attributes of the employment the association and co-workers. According to Rothmann and Coetzer (2003) job performance is a multi-dimensional develops which show how well representatives play out their undertakings the activity they take and the eleverness they appcar in tacking issues. Performance must be recognized from effectiveness and from productivity or efficiency (Sonnentag 2010)